Solvothermal syntheses, crystal structures and properties of four polymers built by p-methoxyphenyl imidazole dicarboxylates. Issue 4 (3rd April 2017) - Liang, Xi; Wang, Jing; Wang, Qi; Zhang, Qingxia; Li, Gang
Abstract: By employing 2-(4-methoxyphenyl)-1H-imidazole-4, 5-dicarboxylic acid ( p -MOPhH3 IDC) to react with Cd(II), Zn(II) and Sr(II) ions, four polymers, [Cd( p -MOPhHIDC)(2, 2′-bipy)]n (2, 2′-bipy = 2, 2′-bipyridine) (1), [Zn0.5 ( p -MOPhH2 IDC)·H2 O]n (2), [Cd4 ( p -MOPhHIDC)4 (C2 H5 OH)2 (H2 O)2 ]·4C2 H5 OH·2H2 On (3) and [Sr2 (H2 MOPhIDC)2 (C8 H4 O4 )(H2 O)6 ]·6H2 On (4) have been solvothermally synthesised and structurally characterised by single-crystal X-ray diffraction. Polymer1 is a chain with 2, 2′-bipy appending in the same side. Polymer2 is a 2D rhombus grid structure. The π⋯π interactions between the aromatic groups supply the additional stabilisation for the solid-state structures of1 and2 . Polymer3 shows a 3D framework bearing 1D open channels. Polymer4 exhibits a 2D latticed plane. The thermal and photoluminescence properties of1 –4 have been investigated as well. Abstract : Four polymers constructed by substituted imidazole dicarboxylates have been afforded and structurally characterized by single-crystal X-ray diffraction. Their thermal properties have been investigated.